DIGITAL NATIVE’S VOICES ON ONLINE PLATFORM IN BLENDED LEARNING - Masyhud Masyhud; Laela Hikmah Nurbatra (IKIP Siliwangi, 2023)
Teachers are required to provide digital learning environment which is fit with digital native learners. Moreover, Digital environment offer various online platforms which can be accessed by digital native learners. Therefore, the aim of this research is to investigate the digital native’s voices on online platforms in blended learning. In regard with the concern, the current research applied a survey research which involves a hundred and fifty two students of English Language Education Department at one of Universities in East Java. In case of instrument, researchers used survey in form of online questionnaire with close-ended questions and rating scales to collect the data. Survey relies on closed-ended questions often use ratings scales. In addition, this research confirmed that the students they cannot decide their position on the function of blended learning along their learning process, 47,4% respondents answered “Maybe”. They also preferred to use Googleclassroom as their learning platform than other platforms. Moreover, Interaction between teacher and students is the main concern in blended learning with 69,6% respondents.